Case Report: Persistent left superior vena cava: an incidental finding during peripherally inserted central catheter placement - Pan, Shi-Xiang; Zhang, Ye-Ling; Fang, Fang (Frontiers in Surgery, 2024)
Background: A peripherally inserted central catheter (PICC) is a specialized type of long-term intravenous catheter commonly employed for administering chemotherapy.The operation and management of PICC should exclusively be carried out by trained healthcare professionals equipped with the requisite knowledge of anatomy, procedural technique and patient care. Persistent left superior vena cava (PLSVC) is a vascular malformation which is typically asymptomatic in clinical presentation, almost always identified during invasive surgery or imaging examinations.Case Presentation: Herein, we detailed a case involving a breast cancer patient whose PLSVC was identified during the placement of PICC because of the negative P-wave in electrocardiogram (ECG). Subsequent examination, including chest X-ray imaging, postoperative enhanced CT of the chest, ECG, and consultation with an experienced imaging physician confirmed that the patient's variant type was PLSVC type Ⅰ.Removal of the catheter was deemed unnecessary, as the catheter tip was appropriately positioned and no other concomitant cardiovascular malformations were detected.The PLSVC is a vascular anomaly and is relatively uncommon within the general population. The operator should possess a thorough familiarity with the potential anatomical variations of left superior vena cava, and specialized case profile should be established for patients diagnosed with PLSVC.